A Novel CeO2-WOx-TiO2 catalyst for high speed shear mixing assisted oxidative-extractive desulfurization of fuel oil - Ligaray, Corazon V. (College of Engineering, University of the Philippines Diliman, 2015)
A series of cerianite, tungstite and titania (CeO2-WOx-TiO2) nanocomposites with different WOx contents have been synthesized by sol-gel method. These nanocomposites catalyst were used for catalytic oxidative extractive desulfurization of fuel oils, which were composed of dibenzothiophene (OBT) dissolved in toluene and real diesel fuel oil. The 30% hydrogen peroxide, H2O2 as oxidant and acetonitrile as extractant. These catalysts were characterized by SEM-EOS. Catalytic oxidation results show that the catalysts have high selectivity in refractory fuel oil with organo sulfur contents. The oxidative removal of OBT increases as the HPW content increases. The nanocomposites CeO2-WOx-TiO2 also shows high selectivity for DBT oxidation in the DBT-toluene acetonitrile system. The catalytic oxidative desulfurization ratio of model fuel reached to 100% with nanocompositesCeO2-WOx-TiO2 (35-30-35) mol percent catalyst nanocomposition under 333 K in 30 minutes.